Charge transport through perylene bisimide molecular junctions: An electrochemical approach. Issue 11 (23rd September 2013) - Li, Chen; Stepanenko, Vladimir; Lin, Mei‐Jin; Hong, Wenjing; Würthner, Frank; Wandlowski, Thomas; Frauenheim, Thomas; Niehaus, Thomas; Repp, Jascha; Richter, Klaus; Weber, Heiko
<x xml:space="preserve">Abstract</x> Single molecular junction conductances of a family of five symmetric and two unsymmetric perylene tetracarboxylic bisimides (PBI) with variable bay‐area substituents were studied employing a scanning tunneling microscope (STM)‐based break junction technique. The stretching experiments provide clear evidence for the formation of single molecular junctions and π–π stacked dimers. Electrolyte gating demonstrates a distinct gating effect in symmetric molecular junctions, which strongly depends on molecular structure and properties of the solvent/electrolyte. Weak π–π‐coupling in the unsymmetric dimers prevents rectification. <inline-graphic xlink:href="ark:/27927/pgg3v1br380" content-type="pssb201350034-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />